Three distinct optical-switching states in phase-change materials containing impurities: From physical origin to material design. (10th June 2021) - Bi, Chaobin; Xu, Kaicheng; Hu, Chaoquan; Zhang, Ling; Yang, Zhongbo; Tao, Shuaipeng; Zheng, Weitao
Graphical abstract: Highlights: Increasing structural disorder difference between phases enlarges optical contrast. Interstitial impurities (like N) are key to realize three optical-switching states. Nitrogen causes grain refinement and lattice distortion structural in cubic phase. Phase change materials with van der Waals gaps in stable phase are potential matrix. Abstract: Ge2 Sb2 Te5 is the most widely utilized chalcogenide phase-change material for non-volatile photonic applications, which undergoes amorphous-cubic and cubic-hexagonal phase transition under external excitations. However, the cubic-hexagonal optical contrast is negligible, only the amorphous-cubic phase transition of Ge2 Sb2 Te5 is available. This limits the optical switching states of traditional active displays and absorbers to two. We find that increasing structural disorder difference of cubic-hexagonal can increase optical contrast close to the level of amorphous-cubic. Therefore, an amorphous-cubic-hexagonal phase transition with high optical contrast is realized. Using this phase transition, we have developed display and absorber with three distinct switching states, improving the switching performance by 50 %. Through the combination of first-principle calculations and experiments, we reveal that the key to increasing structural disorder difference of amorphous, cubic and hexagonal phases is to introduce small interstitial impurities (like N) in Ge2 Sb2 Te5, rather than large substitutional impurities (like Ag) previously thought. This is explained by the formation energy and lattice distortion. Based on the impurity atomic radius, interstitial site radius and formation energy, C and B are also potential suitable impurities. In addition, introducing interstitial impurities into phase-change materials with van der Waals gaps in stable phase such as GeSb4 Te7, GeSb2 Te4, Ge3 Sb2 Te6, Sb2 Te3 will produce high optical contrast amorphous-metastable-stable phase transition. This research not only reveals the important role of interstitial impurities in increasing the optical contrast between metastable-stable phases, but also proposes varieties of candidate matrices and impurities. This provides new phase-change materials and design methods for non-volatile optical devices with multi-switching states.